Formation and Capasity Building Of Herbal Healthy Cadre in Api-Api Village, Wonokerto, Pekalongan Regarding TOGA - Wirasti, Wirasti; Rahmatullah, St.; Permadi, ulian Wahyu (Prosiding University Research Colloquium, 2022)
Village Api-apui Wonokerto Disctrict, Pekalongan Regency located approximately 6 km to the north Pantai Utara Jawa (Pantura). The livelihoods of the Api-api villages community is fisherman, pond farmers, convection farmers, rice farmer ect. The health level of the Api-Api community was initially relatively good because awareness for treatment was good, but after the rob and the covid-19 pandemic, the health of the community village declined and the environment became less well -maintained. To support and further improve the level of public health, it necessary to form herbal healthy cadre. The aim of this activity service community is to increase and empower community in Api-Api Vilage, Wonokerto District, Pekalongan Regency. The Service vommunity is carried out in several stage. The first stage: observation, the second stage is a shared perception with the villagehead, the third stage is counseling on how to plant family medicinal plants (TOGA), the fourth stage is training on how to select and grow medicinal plants. This Methods activity is collaboration with the village govermant and training. The results of this activity is an increase in knowledge and undrstanding of herba; healthy cadres in Api-Api Village by 38,2%. The community (Herbal healthy cadres) incerased their knowledge about how select and grow medicinal plant . The Conclusion this activity is to increase capacity of knowledge plant medicinal and how to select as well as plant TOGA.